Radical gestures: time’s matter for architecture - Jackson, ML (Studies in Material Thinking Journal, 2011)
Confronting the conservative in architecture is a timely and necessary agenda, a confrontation that aims to explore and expose the complex of forces that constitute the discipline, profession and teaching agencies of architecture. With this paper I want to broach three main concerns in addressing the notion of conservatism and conservation within the disciplinary boundaries of architecture. Firstly I want to outline something of the legacy we have to negotiate in this very agenda. This requires some examination of the grounds of modernity as it has set Eurocentrically derived cultures the task of inventing the new. Secondly, we need to develop some understanding of what I am tentatively calling “conserving the present,” that is concerned with examining the uncanniness or unhomliness of our sense of dwelling, which is to say, any sense of identity or being-at-home. Projects of conservation tend to be constituted as prosthetics of forgetting this condition of not-being-at-home. The third part of the paper addresses a question of ethics and architecture, as a problem of constituting practices for a future-to-come. Here there is an attempt to think the question of ethics otherwise than as a legacy of modernity’s Enlightenment thinking, and therefore pose a question of the new in terms other than those of modernity’s notion of progress.
Keywords: Time; Architecture; Modernity; Deleuze; Ethics